2009
DOI: 10.1002/jsfa.3730
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electric field treatment of carrots before drying and rehydration

Abstract: BACKGROUND: In this study the effects of pulsed electric field (PEF) pretreatment were evaluated during drying and rehydration of carrots. Carrots pretreated with an electric field intensity of 1 kV cm −1 (capacitance 0.5 µF, 20 pulses) or 1.5 kV cm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 27 publications
3
18
0
3
Order By: Relevance
“…It can be assumed that the cost of fragmentation of plant material can be decreased as a result of the mechanical properties' alteration, as well. Gachovska et al [33] confirmed this assumption and found that the energy to break point, measured by Instron device, both before dehydration and after rehydration of carrots, significantly differed between untreated, PEF-treated, and blanched material. Interestingly, however, no significant differences have been found within the range of PEF-treated samples, even when the higher electric field strength (from 1 to 1.5 kV=cm) and higher capacitance (from 0.5 to 1 mF) were applied.…”
Section: Dried Materials Propertiessupporting
confidence: 51%
See 1 more Smart Citation
“…It can be assumed that the cost of fragmentation of plant material can be decreased as a result of the mechanical properties' alteration, as well. Gachovska et al [33] confirmed this assumption and found that the energy to break point, measured by Instron device, both before dehydration and after rehydration of carrots, significantly differed between untreated, PEF-treated, and blanched material. Interestingly, however, no significant differences have been found within the range of PEF-treated samples, even when the higher electric field strength (from 1 to 1.5 kV=cm) and higher capacitance (from 0.5 to 1 mF) were applied.…”
Section: Dried Materials Propertiessupporting
confidence: 51%
“…Afterwards, more scientists analyzed the influence of PEF treatment on drying. Gachovska et al [33] studied the impact of PEF and blanching before the convective drying of a carrot. They concluded that both blanching and PEF treatment enhance the drying rate in comparison with intact samples.…”
Section: Drying Coursementioning
confidence: 99%
“…Therefore, the treatments would not affect the visual acceptance of the final product. Contrary results on the effect of heat, high pressure and PEF on rehydration capacity were reported by different working groups for several raw materials (Abe et al, 2011;Ade-Omowaye et al, 2001;Amami et al, 2007;Eshtiaghi et al, 1994;Gachovska et al, 2009;Rastogi & Niranjan, 1998;Taiwo et al, 2002). Differences in product shape, drying technique and rehydration conditions strongly influence the overall rehydration activity and the contribution of pre-processing steps on it.…”
Section: Tablementioning
confidence: 51%
“…(Gachovska, Simpson, Ngadi, & Raghavan, 2009;Martin-Belloso & Sobrino-Lopez, 2011;Puértolas, Cregenzán, Luengo, Álvarez, & Raso, 2013;Soliva-Fortuny, Balasa, Knorr, & Martin-Belloso, 2009; Witrowa-Rajchert, Wiktor, Sledz, & Nowacka, 2014). This emerging technology is based on the application of very short, high voltage pulses to food which is placed between two electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate this parameter, generally the measurement of electrical conductivity or impedance is used. In many cases on the basis of the electrical parameters measurement the cell disintegration indexes are determined (Bazhal, Ngadi, Raghavan and Nguyen, 2003;Ersus et al, 2010;Gachovska et al, 2009;Lebovka, Bazhal, & Vorobiev, 2002;Lebovka, Praporscic, & Vorobiev, 2004a;Wiktor, Witrowa-Rajchert, & Chudoba, 2009). There are also some other indexes which are based on nonelectrical measurements.…”
Section: Introductionmentioning
confidence: 99%